PATHOLOGY OF THE THYROID GLAND IN PATIENTS WITH RHEUMATOID ARTHRITIS (Multidisciplinary Journal of Science and Technology, 2024)
Endocrine disorders are of significant importance in the occurrence and progression of rheumatic diseases. Often, endocrine changes that occur during puberty, menopause, pregnancy, childbirth, and abortion serve as a background for the development of connective tissue diseases [6, 13]. At the same time, changes in neuroendocrine status are an integral component of the progression of rheumatic diseases [2, 5, 14].